Vínculos psicológicos no preparo para o parto humanizado com equipe de assistência ao parto e parturientes - Nahsan, Jordana Luz Queiroz (2022)
This study was done at psychologist post graduation Program of Mato Grosso Federal University. The main purpose was the relationship between parturients and primary care professionals who work with pregnancy and childbirth preparation because it’s understood that childbirth and birth humanization its important for Psychology since humanity relationship is the main path for service being humanized. Therefore, this study asked to know how the connection between the childbirth care team and the pregnant constitutes in an knowledge experience for those pregnant, which feelings, emotions and senses comes up during prenatal period, as how as the emotion attitude team is perceived. Thus, the theory used in this study was the Centered Approach in the Person, a humanist current in Psychology, which focuses on the person of the client and the therapeutic process, in which the concern with the value of the human being and the attempt to understand him in his world and perceptions. Based on this approach, the main reference are the attitudes necessary for a relationship that facilitate human growth as: congruence, unconditional positive regard and empathic understanding. Based on that, the field study can learn how the services offered to these pregnant women were experienced, using the empirical phenomenological method, using interview and psychological listening. Through the qualitative methodology, interviews were done to know the perceptions and experiences of those women with online meetings, four women attended at the same Health center of Mato Grosso capital. The results we’re divided into three parts: 1) Connection in the helping relationship; 2) Perceptions about violence obstetrics; 3) SUS & Facilitating Attitudes. It is noted that connection was brought by them, even partially, an individualized approach, respect for diversity and care. Besides, it was showed that obstetric violence, model of anticipatory interventions at birth, as well as the absence of humanized care with people assisted in the System still exist, mitigating at different times the positive experience of childbirth. Also, at Brazilian health public care, SUS still miss of qualification besides the technique and humanity care in a consistent way. Finally, at reflections from the ACP framework, indicates that there is consonance with the National Primary Care Plan (PNAB) and the recommendations of the World Health Organization (WHO) regarding the importance of the Connection within an empathic relationship, respect, which provides autonomy for the positive experience in childbirth preparation.